Still birth in a tertiary health facility in Enugu state South-East Nigeria: a hidden tragedy - Nwoga, Hope O.; Ajuba, Miriam O.; Igweagu, Chukwuma P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Stillbirth is one of the common adverse outcomes of pregnancy that occur worldwide. The prevalence differs in different continents of the world and even within different localities in the same country. The objective of this study was to determine the prevalence and social determinants of health that affect still birth in Enugu state, Nigeria. Methods: The study was a prospective hospital-based study conducted at the obstetrics and gynecology department of a tertiary health facility in Nigeria. All the data were retrieved from the ante natal and delivery card of all the women that delivered at the unit within the time of data collection. Data was analyzed using SPSS version 25 and variables were presented as frequencies, percentages, means, and standard deviation. Bivariate analysis was done using chi-square test. The level of significance was set at p value≤0.05. Results: The mean age of the mothers was 29.76±4.69 while most of them were aged 21-30 years 431(56.0%). Majority of them were employed 529 (68.7%) and had tertiary education 484 (62.9%). The prevalence of still birth was 40.3 per 1000 births. Maternal age, marital status, educational levels and booking status affected the prevalence of still birth. On logistic regression, un-booked mothers had 25 times odds of having still birth when compared to those that booked after 28 weeks gestation Conclusions: The prevalence of still birth is high in Enugu state with un-booked mothers contributing about 88.6%. Early booking helps to detect possible complications early with timely interventions.